Information technology in a global business environment : readings and cases - Deans, Candace; Jurison, Jaak. (Danvers, MA : Boyd and Fraser, 1996)
This book is about: Globalization of the marketplace; Globalization of the organization; Global information systems and technology: Planning and strategic implications; Global connectivity and telecommunications; Management of global information flows; Integrating technology, systems, and people across the globe; and Selected cases.
Keywords: Business; Management; Information technology; Enterprises; Information technology -- Management -- Case studies; International business enterprises -- Communication systems -- Case studies